Optimization of Slaughter Weight of Black Bengal Goat from Four Agro climatic Zones in the State of West Bengal - Sikder, Sujoy Kumar; Chatterjee, J. K.; Biswas, S.; Das, S.; Biswas, A. K. (Journal of Meat Science, 2017)
The aim of this study was to optimize market slaughter weight of Black Bengal goats reared under extensive managerial practices by the farmers. For this, both male and female goats of different age groups from four different agro-climatic zones were selected and different carcass quality traits and yields of different cut-up parts were determined. Results indicated that sex had direct influence (p0.05) on all thesepa meters.However, age had direct influence on improvement of carcass yields and yields of different primal cuts, since with the increment of age, dressing percentagesand proportionate weights of all the primal cuts were increased. In conclusion, sex and agro-climatic zones showed only little effect on improvement of carcass quality traits, but age has significant influence on increase of carcass yield especially dressing percentage and hot or cold carcass weight. So, slaughtering of 9 months and above age groups of goats may be appropriate for both economy and quality point of view.
Keywords: Black Bengal goat; Slaughter weight; Agro climatic zone; West Bengal